Brush-paintable and highly stretchable Ag nanowire and PEDOT:PSS hybrid electrodes. Issue 1 (December 2017) - Lim, Ji-Eun; Lee, Sang-Mok; Kim, Seok-Soon; Kim, Tae-Woong; Koo, Hyun-Woo; Kim, Han-Ki
Abstract Highly transparent and stretchable Ag nanowire (NW)/poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hybrid electrodes were prepared on stretchable polyurethane substrates by using simple and cost-effective brush painting technique. The optimized Ag NW/PEDOT:PSS hybrid electrode showed a sheet resistance of 19.7 Ohm/square and a high optical transmittance of 88.64% comparable to conventional ITO electrode. It was found that shear stress of the paintbrush led to an effective lateral alignment of the Ag NWs into the PEDOT:PSS matrix during brush painting process. In addition, we investigated mechanical properties of the brush painted Ag NW/PEDOT:PSS hybrid electrode using inner/outer bending test, stretching tests, twisting test and rolling test in detail. The optimized brush painted Ag NW/PEDOT:PSS electrode showed a higher strain (~30%) than brush painted Ag NW or sputtered ITO electrode. Furthermore, we demonstrated the outstanding stretchability of brush painted Ag NW/PEDOT:PSS hybrid electrode in two applications: stretchable interconnectors and stretchable electrodes for stretchable and wearable thin film heaters. These results provide clear evidence for its potential and widespread applications in next-generation, stretchable displays, solar cells, and electronic devices.